Fundamental of Entrepreneurship ENT300 : KBKT Laundry / Erna Xanariah Katusani ... [et al.] - Katusani, Erna Xanariah; Borhan, Nur Aina Maradia; Ruhaidi, Muhammad Hazmi; Zulkiflee, Zainurul Ramadhan; Maktri@Nair, Syandy Meliah (Universiti Teknologi Mara Cawangan Sarawak, 2016)
A busine*s plan is a formal shtemert of a set of business goals the reasorrey are believed attainable and the plan for reaching those goals. It may also contain background infarmation about the organizatirn or team atbmpting to reach those ggals. Business plans may also hrget changes in perception and branding hy ffre customer, ctent, taxpayer, or large community. When the existing of the business is to assume a major change or when planning a new venture and it required 3 to 5 years of business plan. The idea to put together this business plan is to enable the owners to have a more ideas and potential costs and drawbacks to cerhin business decision and help to modify accordingly before implementing this ideas.